Immersion learning activities: developing communicative tasks in the community - Pinto, Jorge (Theory and Practice of Second Language Acquisition, 2018)
This paper examines the out-of-class Portuguese language teaching activities for foreign students learning Portuguese at the Faculty of Arts of the University of Lisbon and their results in the output of learners. Even in contexts of immersion, students have a tendency to focus only on class activities and not on community activities that involve face-to-face contact with native speakers. To change this situation, we have created a new subject, built on task-based language teaching, called "Immersion Activities", for the Portuguese Foreign Language Annual Course. We present the preliminary results of a study carried out with eighty students and twelve teachers, whose objective is to verify up to what extent this subject translates into a more effective learning of the language and if students' perceptions, at the end of the semester, regarding the learning outcomes, coincide or not with those of the teachers. From the results, it is possible to observe that the students’ and teachers’ opinions converge in the same sense: immersion activities provide a better development of students' communicative competence in Portuguese.